If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x+6-4=16+5x=
We move all terms to the left:
3x+6-4-(16+5x)=0
We add all the numbers together, and all the variables
3x-(5x+16)+6-4=0
We add all the numbers together, and all the variables
3x-(5x+16)+2=0
We get rid of parentheses
3x-5x-16+2=0
We add all the numbers together, and all the variables
-2x-14=0
We move all terms containing x to the left, all other terms to the right
-2x=14
x=14/-2
x=-7
| -35=-(5/7)h | | -7(1+2m)=-91 | | 15=4t+5 | | a-25=(5.30)+12 | | 3x+6-4=16+5x+ | | x-12+5x+32=50 | | -4n+11.5=-1/ | | -17=x+(-4) | | -3/4x+11=20 | | 6(1+3v)=-84 | | 25p-25=10p+200= | | 3x+5(x+1)=7.1+5.3(3x+2) | | 2=2+x/4 | | 2x-28=(1/2)3x-40 | | 2^(x-3)=256 | | b-17=-19 | | 2*x+11=7 | | 8y-(5²+2²)=3= | | 2n+8+2n=48 | | -7b-8(b=4)=88 | | n+n1/5=24 | | 3x-5x+1=(2x-1) | | 3x-5=-6+1 | | -12p=3p | | 3x-5=-7+1 | | 3x-5=-5+1 | | 3x-5=-2+1 | | x/2+4=−1 | | 6^2=-36x | | 5x-2x=5+4 | | 3x-5=-1+1 | | 5x-(3x+7)=2x |